Fluctuating potentials in GaAs:Si nanowires: critical reduction of the influence of polytypism on the electronic structure. Issue 8 (1st February 2018) - Ben Sedrine, N.; Ribeiro-Andrade, R.; Gustafsson, A.; Soares, M. R.; Bourgard, J.; Teixeira, J. P.; Salomé, P. M. P.; Correia, M. R.; Moreira, M. V. B.; De Oliveira, A. G.; González, J. C.; Leitão, J. P.
Abstract : The electronic structure of highly Si-doped GaAs NWs is ruled by fluctuating potentials: luminescence intensity increase and polytypism influence reduction. Abstract : In this work, the effects of Si doping in GaAs nanowires (NWs) grown on GaAs (111)B by molecular beam epitaxy with different Si doping levels (nominal free carrier concentrations of 1 × 10 16, 8 × 10 16, 1 × 10 18 and 5 × 10 18 cm −3 ) are deeply investigated using scanning electron microscopy (SEM), transmission electron microscopy (TEM), grazing incidence X-ray diffraction (GID), photoluminescence (PL) and cathadoluminescence (CL). TEM results reveal a mixture of wurtzite (WZ) and zinc-blende (ZB) segments along the NW axis independently of the Si doping levels. GID measurements suggest a slight increase of the ZB fraction with the Si doping. Low temperature PL and CL spectra exhibit sharp lines in the energy range 1.41–1.48 eV, for the samples with lower Si doping levels. However, the emission intensity increases and is accompanied by a clear broadening of the observed lines for the samples with higher Si doping levels. The staggered type-II band alignment only determines the optical properties of the lower doping levels in GaAs:Si NWs. For the higher Si doping levels, the electronic energy level structure of the NWs is determined by electrostatic fluctuating potentials intimately related to the amphoteric behavior of the Si dopant in GaAs. For the heavily doped NWs, the estimated depth of the potential wells is ∼96–117 meV. Our results reveal that the occurrence of the fluctuating potentials is not dependent on the crystalline phase and shows that the limitation imposed by the polytypism can be overcome.